Global Genetic Architecture of an Erythroid Quantitative Trait Locus, HMIP‐2. (29th July 2014) - Menzel, Stephan; Rooks, Helen; Zelenika, Diana; Mtatiro, Siana N.; Gnanakulasekaran, Akshala; Drasar, Emma; Cox, Sharon; Liu, Li; Masood, Mariam; Silver, Nicholas; Garner, Chad; Vasavda, Nisha; et al.
Summary HMIP‐2 is a human quantitative trait locus affecting peripheral numbers, size and hemoglobin composition of red blood cells, with a marked effect on the persistence of the fetal form of hemoglobin, HbF, in adults. The locus consists of multiple common variants in an enhancer region for MYB (chr 6q23.3), which encodes the hematopoietic transcription factor cMYB. Studying a European population cohort and four African‐descended groups of patients with sickle cell anemia, we found that all share a set of two spatially separate HbF‐promoting alleles at HMIP‐2, termed "A" and "B." These typically occurred together ("A–B") on European chromosomes, but existed on separate homologous chromosomes in Africans. Using haplotype signatures for "A" and "B, " we interrogated public population datasets. Haplotypes carrying only "A" or "B" were typical for populations in Sub‐Saharan Africa. The "A–B" combination was frequent in European, Asian, and Amerindian populations. Both alleles were infrequent in tropical regions, possibly undergoing negative selection by geographical factors, as has been reported for malaria with other hematological traits. We propose that the ascertainment of worldwide distribution patterns for common, HbF‐promoting alleles can aid their further genetic characterization, including the investigation of gene–environment interaction during human migration and adaptation.